Cardiovascular Compromise in Children with Neuromuscular Disease with Respiratory Disturbance: An Audit for Better Follow-Up - Rato, João (2020)
Abstract Introduction: Neuromuscular diseases can be followed by cardiomyopathy and/or arrhythmias that have prognostic consequences. Although respiratory failure is the most frequent cause of death in this group of patients, heart disease is independent of ventilatory compromise and should be investigated. We aimed to investigate the cardiovascular follow-up and diagnosis of a population of patients with neuromuscular disease with respiratory compromise. Methods: Digital files of patients with neuromuscular diseases with respiratory compromise, in active follow-up at a pediatric pulmonology unit of a Portuguese tertiary hospital, were reviewed. Data on demographic, neuromuscular diseases and cardiovascular follow-up characteristics were analyzed. Results: All 49 patients with neuromuscular diseases were analyzed. The median age was 14.3 (1.1-25.1) years and 28 (57%) were males. All of the patients had some type of respiratory compromise. Cardiac evaluation was performed in 35 (71%) patients, with at least six to 12 months of interval, and the following diagnoses were ascertained: dilated cardiomyopathy in three patients with Duchenne muscular dystrophy; right ventricular hypertrophy, mild ascending aortic dilatation and left ventricular diastolic dysfunction in three patients with congenital muscular dystrophy; frequent ventricular ectopic beats and left ventricular diastolic dysfunction in two patients with myotonic dystrophy. Only three patients with neuromuscular diseases with predictable cardiovascular involvement had not been evaluated at our center. Discussion: Most of the patients with neuromuscular diseases with a predictable cardiovascular involvement had been evaluated in a cardiology consultation. The cardiovascular changes present in the group of patients evaluated agree with those described in the literature and the patients are followed-up on according to the recommendations. The diagnosis and monitoring of these cardiovascular changes are mandatory in order to control their progression and impact.